Soil Fertility and Nutrient Management on Spodosol for Oil Palm - Kasno, Antonius; Subardja, Djadja (AGRIVITA, Journal of Agricultural Science, 2010)
The research was carried out in Oil Palm Plantation in Ngabang, Landak Distric, West Kalimantan in May 2008. Composite soil samples were taken from the soils, in which the oil palms indicated the nutrient disorders. The aims of the research were to study the soil fertility and nutrient management of Spodosols for oil palm crops. The results indicated that spodic horizons in the oil palm plantation varied between 30 and 70 cm. Besides spodic horizons, the albic horizon, the horizon that cant be penetrated by the crops root, was also found. The texture is sandy with the sand content about 69-98 %. The soil has acidic properties, C organic varied from low to high, low phosphate, potassium, magnesium and Cation Exchange Capacity. In contrast, in the spodic horizon, the content of organic carbon, total nitrogen and CEC were higher, as well exchangeable Aluminum. There was close relationship between soil organic carbon and nitrogen and CEC in the soil. It is advice not to use spodosols for food crop and estate crops. The application of slow release fertilizers combined with organic fertilizers is highly input when oil palm planted on the Spodosol.Keywords: Spodosols, soil characteristic, oil palm